2021
DOI: 10.1016/j.wjorl.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Laser vs microdebrider eustachian tuboplasty for the treatment of chronic adult eustachian tube dysfunction: A systematic review

Abstract: Objectives Multiple treatments are described in the literature for the treatment of chronic Eustachian tube dysfunction but high-level quality evidence seems missing to support these treatments. This systematic review aimed to determine and compare the safety and efficacy of Laser Eustachian tuboplasty and Microdebrider Eustachian tuboplasty as a treatment for long-term Eustachian tube dysfunction. Data sources A total of 12 electronic databases were searched up to Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Given the critical condition of ICU patients and their pain and intolerance towards nasointestinal tube implantation, propofol was used for sedation, sufentanil for auxiliary analgesia, and metoclopramide administered orally to prevent nausea and vomiting caused by tube implantation. [ 31 , 32 ][33] The results suggested that B-ultrasound-assisted nasointestinal tube insertion was superior to blind insertion regarding the time to reach the target nutritional value. Furthermore, B-ultrasound-guided intragastric water injection for nasointestinal tube placement could potentially shorten the time to reach target nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical condition of ICU patients and their pain and intolerance towards nasointestinal tube implantation, propofol was used for sedation, sufentanil for auxiliary analgesia, and metoclopramide administered orally to prevent nausea and vomiting caused by tube implantation. [ 31 , 32 ][33] The results suggested that B-ultrasound-assisted nasointestinal tube insertion was superior to blind insertion regarding the time to reach the target nutritional value. Furthermore, B-ultrasound-guided intragastric water injection for nasointestinal tube placement could potentially shorten the time to reach target nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…Eustachian tube dysfunction is defined by signs and symptoms of pressure dysregulation in the middle ear such as ‘aural fullness’, ‘popping’, discomfort, pain or ‘under water sensation’ 11 and represents a common problem with reported incidences ranging from 0.9% to 5%. 19 …”
Section: Discussionmentioning
confidence: 99%
“…26 Present evidence to support its alternatives, such as laser Eustachian tuboplasty and microdebrider Eustachian tuboplasty, is limited in quantity and of poor quality. 19 Although Sadé described cases of a ballooning tympanic membrane returning to its physiological level after being punctured, 17 we do not recommend this approach.…”
Section: Treatmentmentioning
confidence: 92%
See 2 more Smart Citations